Analysis of the Role of Service Systems, Quality and Price on Customer Satisfaction at UPPKB in North Jakarta - Hendy Tannady (Jurnal Multidisiplin Madani, 2023)
The study was conducted to determine the effect of facilities, quality and service prices on customer satisfaction. This type of research is descriptive quantitative. The sampling technique used is Accidental Sampling which is sampling based on any member of the population who coincidentally meets the researcher and can provide the necessary information. The data analysis method was carried out by analyzing the path diagram data. The results show that service facilities have a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction, price has a positive and significant effect on customer satisfaction at the Motor Vehicle Testing Management Unit of Kedaung Angke, DKI Jakarta Provincial Transportation Service